ECTHR_COMMITTEE 57456/18 vom 25. November 2025 , AFFAIRE NICULAE c. ROUMANIE - Ecthr Committee (2025)
Violation de l'article 8 - Droit au respect de la vie privée et familiale (Article 8-1 - Respect de la vie privée); Violation: 8;8-1